1982
DOI: 10.1111/j.1399-0039.1982.tb01463.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐A, B, C, DR antigens, Bf, C4 and glyoxalase I (GLO) polymorphisms in French Basques with insulin‐dependent diabetes mellitus (IDDM)

Abstract: The Basques were previously shown to present a high frequency of HLA-B18 and BfF1, which are known to be associated with insulin dependent diabetes mellitus (IDDM). During the VIII International Histocompatibility Workshop, we studied HLA-A, B, C, DR; Bf, C4 and GLO.I polymorphisms in 51 unrelated French Basque IDDM patients and in 50 controls. Haplotypes were established by family studies in all controls and some patients. Two haplotypes were frequently found in the controls: HLA-A1, Bw57, BfS, C4 F1S, DR7 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…The frequency of homozygous null C4B phenotypes was reported to be increased in patients with IgA nephropathy (IgAN) and Henoch-Schonlein purpura nephritis (HSPN) [1], The high frequency of partial complement 4 (C4) defi ciency was also reported in patients with such autoimmune diseases as systemic lupus erythematosus [2][3][4], insulin-de pendent diabetes mellitus [5][6][7] and Graves' disease [8], Two extended hyplotypes, HLA-A1, Cw7, B8, C4AQ0, C4BI, Accepted : October 23.1992 DR3 and HLA-A30, Cw5. B18, C4A3, C4BQ0, DR3, are known to be associated with such autoimmune diseases, and there has been a debate about the relative importance between the C4 null alleles and the HLA antigens in the pathogenesis of the diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of homozygous null C4B phenotypes was reported to be increased in patients with IgA nephropathy (IgAN) and Henoch-Schonlein purpura nephritis (HSPN) [1], The high frequency of partial complement 4 (C4) defi ciency was also reported in patients with such autoimmune diseases as systemic lupus erythematosus [2][3][4], insulin-de pendent diabetes mellitus [5][6][7] and Graves' disease [8], Two extended hyplotypes, HLA-A1, Cw7, B8, C4AQ0, C4BI, Accepted : October 23.1992 DR3 and HLA-A30, Cw5. B18, C4A3, C4BQ0, DR3, are known to be associated with such autoimmune diseases, and there has been a debate about the relative importance between the C4 null alleles and the HLA antigens in the pathogenesis of the diseases.…”
Section: Introductionmentioning
confidence: 99%
“…This study brings some evidence that not only the B18,BfF1 haplotype, as suggested in previous studies [9][10][11][12][13], but also the silent complement factor allele C4BQO by itself characterise a particularly early-onset form of Type 1 diabetes occurring mostly before 6 years of age. Conversely, the B8, DR3 haplotype has been observed to occur more often in patients older than 6 years at onset.…”
Section: Discussionmentioning
confidence: 50%
“…The most widely confirmed association is that of early onset with the properdin factor B allele BfF1 [9][10][11][12]. In a previous study [13], we also have found a strong association with HLA-B18 but not with the B18,BfF1,DR3 haplotype, possibly because of the small sample size.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…In fact, long genomic extensions termed conserved extended haplotypes (CEH) or ancestral haplotypes that have been maintained unaltered during human evolution are characteristic of this genomic region (4). A particular HLA-DR3 CEH (A*30-B*18-MICA*4-F1C30-DRB1*0301-DQB1*0201-DPB1*0202, or B18-DR3) that is relatively common in southern European populations, has been shown to be conserved across a 5 Mb region and to be more diabetogenic than other HLA-DR3 chromosomes (5,6). These findings support the hypothesis that B18-DR3 chromosomes carry additional risk alleles in other susceptibility loci , which are fixed in all B18-DR3 CEHs, but may not be always present in other less-predisposing DR3 chromosomes.…”
Section: Introductionmentioning
confidence: 99%